Penerapan Disiplin sebagai Strategi Pembinaan Pendidikan Karakter pada Anak Usia Dini : Analisis Teoritis dan Praktis - Cindy Syafatur Rohmah; Nuraida Edlin Hafizah; M. Sopyan Harianto; M. Nafi’ul ‘Ulum; Himia Rina; Mu’alimin Mu’alimin (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The application of discipline as a character education training strategy in early childhood plays a crucial role in shaping children's personality, behavior, and social skills. This study aims to analyze theoretically and practically how discipline can be applied as a character formation strategy in early childhood, considering the role of the family and school environment. The research method uses a qualitative approach through a literature review of 15 Sinta-accredited journal articles in 2020–2024. The results of the study show that positive discipline based on examples, praise, and behavioral habits is more effective than the punishment approach. Families and schools play a role as the main environment in instilling discipline values, although there are still gaps in the application of practices and adaptations in various socio-cultural contexts. This study recommends collaboration between parents and teachers, the development of creative strategies in schools, and the need for further, more in-depth research to optimize the application of discipline as a foundation for character formation in early childhood